Legal Documents Repository Systems - Doddy Ridwandono; Mohamad Irwan Afandi; Eka Dyar Wahyuni; Eklesia Simaremare; Icha Sinaga (Future Science, 2022)
Things that need to be revealed from legal documents are semantics, structure, and relationship between legal documents. We argue that structure and relationships between documents are fundamental. The abundance of legal documents comes from various sources pose a challenge for an institution to maintain cohesion between internal and external legal documents. This study contributes in the form of a system which is able to manage various types of legal documents and their hierarchy, the form of relations between legal documents and the parties involved and also the status of a legal document. Our study was developed based on Indonesian Ministerial Regulation no. 3 of 2021 concerning Manuscripts of the Indonesian Ministry of Education and Culture. The system was developed on a web-based platform, with generic data model designed, and oriented to be able to be adopted by any organization. Discussions and potential system development are discussed at the end of this paper.